2013
DOI: 10.4103/2249-4847.116407
|View full text |Cite
|
Sign up to set email alerts
|

Importance of obtaining lumbar puncture in neonates with late onset septicemia a hospital based observational study from north-west India

Abstract: Objectives:The objective of this study was to estimate the prevalence of meningitis in cases with late onset septicemia (LOS).Materials and Methods:A prospective study was carried out for a period of 1 year in a tertiary care hospital in North West India to estimate the prevalence of meningitis in cases of LOS. In all the admitted neonates with features of sepsis with a positive C-reactive protein, a lumbar puncture (LP) was carried out and results interpreted on the basis of cerebrospinal fluid (CSF) cytology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Similar observation has been made earlier from India6. In the present study, only 12 per cent cases showed increased CSF protein and 7.5 per cent showed decreased glucose.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Similar observation has been made earlier from India6. In the present study, only 12 per cent cases showed increased CSF protein and 7.5 per cent showed decreased glucose.…”
supporting
confidence: 93%
“…In our study, 68.6 per cent neonates with microbiologically proven meningitis were males; and 54 per cent were of low birth weight (LBW), 11 per cent were very LBW and 28 per cent were pre-term. Kaul et al 6 have also observed high frequency of meningitis and sepsis among LBW neonates. A. baumannii , Klebsiella , CoNS and Enterococcus were common bacterial isolates in our study similar to other studies from India 4 15 .…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Around 22% prevalence of meningitis is seen in cases of late-onset sepsis, though the incidence of meningitis in neonatal sepsis is 0.3%–3%. [ 21 ] In this study also, the preterm neonates and those with a risk factor including chorioamnionitis or abscess have shown coexistence of meningitis. The CSF cytology and cell count, CSF neutrophils, blood neutrophil percentage, and CRP showed to have a good correlation with meningitis in this study, particularly in the appropriate clinical setting.…”
Section: Discussionsupporting
confidence: 51%
“…Neonatal meningitis has been linked to a 33-48 % mortality rate in developing countries while these estimates are around 10% in developed countries (6) . According to earlier studies meningitis affects about 0.3-3 percent of neonates with sepsis, while the incidence of meningitis in neonates with LOS is much greater, reaching up to 30 percent (11,17) . According to Roshi et.al.…”
Section: Discussionmentioning
confidence: 97%